2022
DOI: 10.1515/arh-2022-0124
|View full text |Cite
|
Sign up to set email alerts
|

Structure of pumpkin pectin and its effect on its technological properties

Abstract: The aim of this work is to investigate the structural features, physicochemical, rheological, and emulsifying properties of pectin extracted from pumpkin “Cucurbita maxima” pulp and peel. After the peel and pulp of fresh pumpkin were solubilized in water at high temperature (80°C) and clarification, the obtained filtrate was treated with aluminum sulphate, which precipitates a fibrous coagulum. The results found that the major functional groups of pectin isolates identified by Fourier transform infrared are: –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The data obtained from the analysis of mechanical and barrier properties were within the acceptable range and therefore this pectin can be successfully used as film for food application [29]. Moreover, pumpkin pectin (1% w/w) possessed strong emulsifying activity and could be used to substitute Arabic gum (15%, w/w), soybean soluble polysaccharides, or other types of emulsifiers used at concentrations greater than 1% [65].…”
Section: Cucurbit Fruit Wastementioning
confidence: 74%
“…The data obtained from the analysis of mechanical and barrier properties were within the acceptable range and therefore this pectin can be successfully used as film for food application [29]. Moreover, pumpkin pectin (1% w/w) possessed strong emulsifying activity and could be used to substitute Arabic gum (15%, w/w), soybean soluble polysaccharides, or other types of emulsifiers used at concentrations greater than 1% [65].…”
Section: Cucurbit Fruit Wastementioning
confidence: 74%
“…As shown in the FTIR spectra of the polymers (Figure 2), all of the copolyesters exhibited the following characteristic absorption peaks: 3073 cm À1 (aromatic C-H stretching vibration), 1735 cm À1 (ester C O stretching vibration), 1629, 1599, 1504, and 1471 cm À1 (C-C aromatic). 23,24 The peaks at 1179-1155 cm À1 and 1048-1011 cm À1 were attributed to asymmetrical and symmetrical C-O-C stretching vibrations, respectively. 25 The characteristic peak corresponding to a para-substituted aromatic structure at 883 cm À1 indicated that 4-HNA had been successfully grafted into the ternary copolyester.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…The close resemblance of HAP to bones and teeth makes this material useful as an implant for dental and orthopedic applications [1][2][3]. Because of the HAP's poor mechanical qualities, significant improvements are achieved by adding various dopants like ZnO, ZrO2, Fe3O4, and Li to HAP [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Htun et al [2] discovered that reinforced CaO-ZrO2/HAP is an effective material for improving the strength and toughness of the selected bio-composites.…”
Section: Introductionmentioning
confidence: 99%